Association between External Load and Injury Incidence in Professional and Elite-Youth Football Players - Georgiadis, Georgios; van Gaal Appelhof, Rainer; Stoop, Rick; Peters, Jeroen; Essers, Johannes (CV Rezki Media, 2024)
Background: Elite football players are monitored daily to minimize injury risks and maximize performance. Objectives: The aim of the study was to investigate injury incidence differences between competition and training and differences in key external load indicators during 1-, 2-, 3- or 4-weeks prior to the injury (WPI) with respect to the season average week (SAW). Methods: Data of 224 unique players of five teams (1st, under-23, under-18, under-17, and under-16) were collected during 3.5 seasons of competition and training resulting in 467 player records in total. Collected data included kinematics from Global Positioning System tracking units (Viper Units, STATSports) and 528 injury incident records. External load was expressed in terms of acceleration counts (ACC), deceleration counts (DEC), total training time (TT), total distance (TD), and distance covered in high-speed zones: 14.4-19.7 km/h (Z4), 19.7-25.1 km/h (Z5), and >25.1 km/h (Z6). Injury incidence was derived as number of injuries per 1000 hours of exposure. Results: Incidence rate was on average 4-11 times higher during competition than training for all teams except under-16 (incidence rate: 2.5, p=.153). In the 1st Team, external load (i.e. ACC, TT, and TD) were significantly different between 1-, 2-, 3-, and 4-WPI and SAW (p=.041, p=.037, and p=.049 respectively). For ACC and TT, the 3-WPI loads, were significantly higher than during SAW (p=.044 and p=.038, respectively). Conclusion: These findings can assist professionals and scientists to improve their understanding of the relationship between external load indicators and injury incidence and consequently improve player health and performance.